Managerial Training Dalam Pengelolaan dan Peningkatan Produktivitas Usaha Bumdes di Desa Bermi, Demak - Gunawan Mohammad; Dwi Retna Sulistyawati; Dyah Ayu Nurwidyaningsih; Decky Rochmanto; Maulida Azizan Najwa (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2025)
Bermi Village is one of the villages in Mijen District, Demak Regency. The existence of Bumdes in a village is currently important for the development and independence of the village. With quite a lot of village potential, including Sumur Gandeng, onion farmers, rice farmers, water hyacinth craftsmen groups, catering, and waste that is not managed properly. However, until today the lack of good management has become an obstacle for Bumdes in Bermi Village. In terms of legal aspects, improvements need to be made, and there are no productive businesses operating from the potential of Bermi Village. Based on this background, this service aims to help Bermi Village in increasing knowledge of Bumdes management, by conducting socialization and Discussion (Focus Group Discussion) of village potential which is used as a productive business plan to be implemented. The results of this service, as many as 92% of participants stated that they understood and understood the socialization given (with details of 35% very understanding, and 58% understanding), and it was decided that several business plans that would be implemented were the management of Bumdes cooperatives for productive businesses, management of Sumur Gandeng as a tourism business, and management of village-level waste as a form of non-productive Bumdes business. So that with this service, Bumdes becomes well organized in organizational administration.